Design and Simulation of Cultivating Machine for Double Digging Planting Technique - Zazali, Mohamad Aqmal Fikry; Johar, Muhammad Akmal (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Agriculture sector is a crucial sector that plays an important role on Malaysia economic. Malaysia agriculture farmers and gardeners facing the same problem when it comes to preparing crops soil where it consumes too many man-hours to complete. Tillage needed to be implemented to the soil as preparation by mechanical agitation of various types such as digging, ploughing, overturning, and stirring. Double digging is one of a new forms of deep tillage where it utilizes compost and mulch to enhance crops productions. This study aims to increase soil drainage and aeration on two layers of various types of soil and to create a machine simulation model and design which will ease farmers loosing packed soil during farming. In this context, a machine design and simulation will be made by using Solidworks 2020 software in order to obtain a 3-dimensional product drawing. To test either the machine fail or success when operating, simulation needs to be done to roughly see how the machine will buckle and bend when various types of load and stress are applied on a certain parts of machine body frame. The results showed there will be a small amount of bending due to the weight of the machine motor and rigger. Plus, the materials chosen are compatible to handle all stress, strain and high factor of safety on the body frame.